1985
DOI: 10.1212/wnl.35.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of high‐incidence amyotrophic lateral sclerosis and parkinsonism‐dementia on Guam

Abstract: The high incidence rates of amyotrophic lateral sclerosis (ALS) and parkinsonism-dementia (PD) occurring among the Chamorros of Guam have declined to rates only slightly higher than those observed in the continental United States. This decline has occurred principally among males, especially those born after 1920 and living in areas where calcium and magnesium levels are low in soil and water. The male-to-female ratio among affected patients now approaches unity, compared with ratios of 2 to 1 for ALS and 3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(84 citation statements)
references
References 0 publications
7
75
2
Order By: Relevance
“…Mg 2ϩ in the water supply is similarly low, about 10-fold lower in the South. This hypothesis also helps explain the observed decline of ALS-G and PD-G in recent years in parallel with modernization (6,30) with the accompanying changes in diet as well as the establishment of a treated water supply system. A check of the SNP database reveals that the T1482I variant of 1403-1864).…”
Section: Resultsmentioning
confidence: 84%
“…Mg 2ϩ in the water supply is similarly low, about 10-fold lower in the South. This hypothesis also helps explain the observed decline of ALS-G and PD-G in recent years in parallel with modernization (6,30) with the accompanying changes in diet as well as the establishment of a treated water supply system. A check of the SNP database reveals that the T1482I variant of 1403-1864).…”
Section: Resultsmentioning
confidence: 84%
“…The average annual incidence of PDC per 100,000 for the period 1960-1979 declined from 55 to 25 for men, but only from 23 to 21 for women. In 1985, Garruto et al [29] reported a similar magnitude of decline in the age-adjusted incidence rates for men and women. Results of a 15-year follow-up study in 1983 of a random sample of adult Chamorros from all villages on Guam reported conflicting findings.…”
Section: Pathologymentioning
confidence: 89%
“…The disorder is found together with a second high-incidence disease, amyotrophic lateral sclerosis (ALS). The incidence of both diseases has declined dramatically over the past half century, suggesting an environmental etiology (1). The neuropathology of PD is hallmarked by neurofibrillary tangles (NFTs) (2) of paired helical filaments (PHFs) composed of abnormally hyperphosphorylated forms of the microtubule-associated protein tau.…”
mentioning
confidence: 99%